Penerapan Metode Tanya Jawab Berbasis Nilai Islam Pada Materi Kebersihan Lingkungan Untuk Meningkatkan Motivasi Belajar Anak Usia Dini - Yuliana; Syamsul Hadi; Neli Aprianti (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2024)
With the question-and-answer method, children prefer or feel more curious, when cleaning while singing children are motivated in learning, this method will be able to collaborate learning by playing with their friends, parents, teachers or surrounding objects, which can provide strategies in motivating children's learning. Children can social development from the environment in the form of encouragement or motivation can foster children's learning development. The purpose of writing this thesis is: “To Apply the Islamic Value-Based Question and Answer Method on Environmental Hygiene to Increase Early Childhood Learning Motivation at KB AL-Wafa Ganjar. This study uses classroom action research using the Kemmis and Mc. Taggart research model. This research was conducted in 2 cycles and a pre-cycle stage, in 1 cycle three meetings were held. As the subject of research for children aged 5-6 years as many as 10 children, 6 boys and 4 girls. Data collection techniques with observation sheets and documentation during the learning process. The results of the research obtained at the pre-cycle stage amounted to 70%, in cycle I experienced an increase of 75%, then the researcher continued with the cycle II stage. At the second cycle stage, it increased to 85%. From these results it can be concluded that the learning motivation of children aged 5-6 years can increase with the question-and-answer method. The success of increasing this research by preparing hygiene tools and songs about hygiene is interesting, creating a fun, creative and innovative learning atmosphere.